Different trajectories in upper limb and gross motor function in spinal muscular atrophy. Issue 5 (9th August 2021) - Coratti, Giorgia; Pera, Maria Carmela; Montes, Jacqueline; Pasternak, Amy; Scoto, Mariacristina; Baranello, Giovanni; Messina, Sonia; Dunaway Young, Sally; Glanzman, Allan M.; Duong, Tina; De Sanctis, Roberto; Mazzone, Elena Stacy; et al.
Abstract: Introduction: The Hammersmith Functional Motor Scale Expanded (HFMSE) and the Revised Upper Limb Module (RULM) have been widely used in natural history studies and clinical trials. Our aim was to establish how the scales relate to each other at different age points in spinal muscular atrophy (SMA) type 2 and 3, and to describe their coherence over 12 mo. Methods: The study was performed by cross‐sectional and longitudinal reanalysis of previously published natural history data. The longitudinal analysis of the 12‐mo changes also included the analysis of concordance between scales with changes grouped as stable (±2 points), improved (>+2) or declined (>−2). Results: Three hundred sixty‐four patients were included in the cross‐sectional analysis, showing different trends in score and point of slope change for the two scales. For type 2, the point of slope change was 4.1 y for the HFMSE and 5.8 for the RULM, while for type 3, it was 6 y for the HFMSE and 7.3 for the RULM. One‐hundred‐twenty‐one patients had at least two assessments at 12 mo. Full concordance was found in 57.3% of the assessments, and in 40.4% one scale remained stable and the other changed. Each scale appeared to be more sensitive to specific age or functional subgroups. Discussion: The two scales, when used in combination, may increase the sensitivity to detect clinically meaningful changes in motor function in patients with SMA types 2 and 3. Abstract : See Editorial on pages 639–640 in the December issue .